The Role of Information and Communication Technology in Improving the Efficiency of Human Resource Management Administration - Sutrisno Sutrisno (Politeknik Ganesha Medan, 2023)
The use of ICT has fundamentally changed the way organisations work and operate in various sectors, including HRM. Along with technological advancements, organisations across industries have adopted various ICT solutions to improve efficiency and productivity in HRM administration processes. The role of ICT in improving HRM administration efficiency is increasingly recognised as a key element in achieving organisational success in this digital era. This research aims to explore relevant studies and literature on how ICT has influenced and improved HRM administration efficiency in various organisations. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. This study arrived at a discovery that the role of ICT in improving the efficiency of HRM administration has become something that cannot be ignored. The application of technology in HRM provides various benefits to organisations, including more efficient employee recruitment and selection processes, automation of administrative tasks, more affordable and accessible employee training and development, and more secure and integrated employee data management.